Human T cell leukaemia virus type 2 tax protein mediates CC‐chemokine expression in peripheral blood mononuclear cells via the nuclear factor kappa B canonical pathway. (January 2014) - Barrios, C. S.; Castillo, L.; Zhi, H.; Giam, C.‐Z.; Beilke, M. A.
Summary Retroviral co‐infections with human immunodeficiency virus type‐1 (HIV‐1) and human T cell leukaemia virus type 1 (HTLV‐1) or type 2 (HTLV‐2) are prevalent in many areas worldwide. It has been observed that HIV‐1/HTLV‐2 co‐infections are associated with slower rates of CD4+ T cell decline and delayed progression to AIDS. This immunological benefit has been linked to the ability of Tax2, the transcriptional activating protein of HTLV‐2, to induce the expression of macrophage inflammatory protein (MIP)‐1α/CCL3, MIP‐1β/CCL4 and regulated upon activation normal T cell expressed and secreted (RANTES)/CCL5 and to down‐regulate the expression of the CCR5 co‐receptor in peripheral blood mononuclear cells (PBMCs). This study aimed to assess the role of Tax2‐mediated activation of the nuclear factor kappa B (NF‐κB) signalling pathway on the production of the anti‐viral CC‐chemokines MIP‐1α, MIP‐1β and RANTES. Recombinant Tax1 and Tax2 proteins, or proteins expressed via adenoviral vectors used to infect cells, were tested for their ability to activate the NF‐κB pathway in cultured PBMCs in the presence or absence of NF‐κB pathway inhibitors. Results showed a significant release of MIP‐1α, MIP‐1β and RANTES by PBMCs after the activation of p65/RelA and p50. The secretion of these CC‐chemokines was significantly reduced (P < 0·05) by canonical NF‐κB signalling inhibitors. In conclusion, Tax2 protein may promote innate anti‐viral immune responses through the activation of the canonical NF‐κB pathway.